Future Morality - Edmonds, David (Oxford University Press, 2021)
The world is changing so fast that it's hard to know how to think about what we ought to do. We barely have time to reflect on how scientific advances will affect our lives before they're upon us. New kinds of dilemma are springing up. Can robots be held responsible for their actions? Will artificial intelligence be able to predict criminal activity? Is the future gender-fluid? Should we strive to become post-human? Should we use drugs to improve our intimate relationships - or to reduce crime? Our intuitions about questions like these are often both weak and confused. David Edmonds has put together a philosophical task force to get to grips with these challenges. Twenty-nine philosophers present provocative and engaging pieces about aspects of life today, and life tomorrow - birth and death, health and medicine, brain and body, personal relationships, wrongdoing and justice, the internet, animals, and the environment. The future won't look the same when you've finished this book.